Conflict, food insecurity, and globalization - Messer, Ellen; Cohen, Marc J. (International Food Policy Research Institute, 2006)
For more than two centuries, proponents and critics of an open global economy have debated whether the free flows of goods, services, and capital make the world more peaceful and food secure or instead exacerbate inequalities and hardships, fanning interclass or interethnic violence motivated by grievance and greed. Food security and pri-mary agricultural commodities have been largely left out of these discussions; the authors begin to fill these gaps... the paper recommends four agendas for further food policy consideration: first, more attention to equitable outcomes in food distribution and food production and trade programs, so that such food security programs do not further contribute to ethnic divisions favoring violence-prone grievance and greed. Second, more careful scrutiny of national marketing and financial policies that influence farmer and middlemen income, and who benefits from agricultural export crops. Third, the design of some type of compensation fund for sudden or certain “losers” in globalization, who face loss of livelihood and recruitment to violence when cash crops like coffee fail to deliver expected livelihoods. Fourth, and in sum, more systematic use of livelihood-security and rights-based frameworks that address local-level food security in the context of national food policy planning